Rudolf Schlechter's South-American orchids IV. Schlechter's "network": Venezuela and Colombia - Ossenbach, Carlos (Universidad de Costa Rica, 2021)
The fourth chapter of the series about Rudolf Schlechter’s South-American orchids again presents abridged biographical information about the botanists and orchid collectors that formed part of Schlechter’s South-American network and who traveled and worked in those countries on the continent’s northern and Caribbean coasts, through Venezuela and Colombia. In the case of Colombia, we cross the isthmus of Darien and arrive for the first time on the Pacific coast of South America. As in other chapters, brief geographical and historical introductory outlines are presented for each of these countries, followed by a narrative on those orchidologists who visited the area, chronologically by the dates of their botanical collections. Keywords/Palabras clave: biography, biografía, history of botany, historia de la botánica, Orchidaceae For accessing the high-resolution PDF, please follow this link: https://n9.cl/13ugw